Effectiveness of Bath Wipes After Hematopoietic Cell Transplantation: A Randomized Trial. (November 2020) - Kjellin, Margie; Qudeimat, Amr; Browne, Emily; Keerthi, Dinesh; Sunkara, Anusha; Kang, Guolian; Winfield, Alicia; Giannini, Mary Anne; Maron, Gabriela; Hayden, Randall; Leung, Wing; Triplett, Brandon; et al.
Objective: Bacteremia is a leading cause of morbidity and mortality in children undergoing hematopoietic cell transplantation (HCT). Infections of vancomycin-resistant enterococci (VRE) and multidrug resistant (MDR) gram-negative rods (GNRs) are common in this population. Our objective was to assess whether experimental bath wipes containing silver were more effective than standard bath wipes containing soap at reducing skin colonization by VRE and MDR GNRs, and nonmucosal barrier injury bacteremia.Study Design: Patients undergoing autologous or allogeneic HCT in a tertiary referral center were randomized to receive experimental or standard bath wipes for 60 days post-HCT. Skin swabs were collected at baseline, discharge, and day +60 post-HCT. The rate of VRE colonization was chosen as the marker for efficacy.Results: Experimental bath wipes were well tolerated. Before the study, the rate of colonization with VRE in HCT recipients was 25%. In an interim analysis of 127 children, one (2%) patient in the experimental arm and two (3%) in the standard arm were colonized with VRE. Two (3%) patients had nonmucosal barrier injury bacteremia in the standard arm, with none in the experimental arm. MDR GNRs were not isolated. The trial was halted because the interim analyses indicated equivalent efficacy of the two methods.Conclusions: Skin cleansing with silver-containing or standard bath wipes resulted in very low and equivalent rates of bacteremia and colonization with VRE and MDR GNRs in children post-HCT. Future studies in other high-risk populations are needed to confirm these results.